2021
DOI: 10.1080/10439463.2021.1916492
|View full text |Cite
|
Sign up to set email alerts
|

Policing the COVID-19 pandemic: police officer well-being and commitment to democratic modes of policing

Abstract: Police organisations have a wealth of experience in responding to emergencies, but COVID-19 is unprecedented in terms of the speed, scale and complexity of developing doctrine and its implementation by officers. The crisis also threw into sharp relief the fact that police policy and, crucially, practice are always implemented within wider social, political and economic contexts. Using online survey data collected from 325 police officers based at forces operating across different UK contexts (cities, conurbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 49 publications
0
41
2
1
Order By: Relevance
“…Few research studies relied on front-line officers' perceptions and experiences. In fact, we are only aware of one published study from the United Kingdom where the unit of analysis was the individual officer (Kyprianides et al , in press). It found that a positive organizational climate was associated with increased police officer health and well-being.…”
Section: The Impact Of Covid-19 On American Law Enforcementmentioning
confidence: 99%
“…Few research studies relied on front-line officers' perceptions and experiences. In fact, we are only aware of one published study from the United Kingdom where the unit of analysis was the individual officer (Kyprianides et al , in press). It found that a positive organizational climate was associated with increased police officer health and well-being.…”
Section: The Impact Of Covid-19 On American Law Enforcementmentioning
confidence: 99%
“…These measures in response to the pandemic push us to rethink some fundamental questions on public policy: the roles of government in services delivery, ways to arrange services, and prioritization of beneficiaries (N. W. M. Wong et al, 2022 ). Scholars have studied the model of antipandemic strategies in Asia (Choi, 2020 ; Hartley & Jarvis, 2020 ; Ho & Chan, 2021 ; Hsieh et al, 2021 ; Huang, 2020 ; Wan et al, 2020 ; Woo, 2020 ; Yuen et al, 2021 ); the antagonism between pandemic control and individual rights (the use of big data and information technology for the surveillance of potential virus carriers); challenges in policing and public accountability (the extraordinary policing tasks of enforcing lockdowns and social distancing legislation by police officers); unemployment/underemployment problems (business suspensions and closures); family and mental health issues (prolonged class suspensions, work‐from‐home arrangements, home quarantines, bans of intra/interfamily gatherings and border closures), and so on (Alcadipani et al, 2020 ; Brooks & Lopez, 2020 ; Chan et al, 2021 ; Farrow, 2020 ; Ho et al, 2020 ; Kyprianides et al, 2021 ). Findings from these emerging scholarly analyses could be important tips for policymakers to respond to the quickly transforming society in the post‐COVID era.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst much research has, quite rightly, focused on the impact of the current crisis on healthcare professionals, less attention has been given to the impact of COVID-19 on other public sector personnel such as police officers ( Alcadipani et al, 2020 ). Nonetheless, some research has already been conducted on policing during the pandemic; with several studies focussing on practical responses to the immediate challenges faced by the police, such as the impact of social distancing on crime or access to personal protective equipment (PPE), whilst others have taken a more humanistic approach by examining the impact of COVID-19 on officer health and wellbeing ( De Camargo, 2021a , 2021b ; Frenkel et al, 2021 ; Langton et al, 2021 ; Kyprianides et al., 2021 ; Laufs and Waseem, 2020 ; Mohler et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In summary, whilst exposure to traumatic events is considered as routine within UK policing and recent research has documented the detrimental impact of the global pandemic on the general health and wellbeing of officers ( De Camargo, 2021b ; Frenkel et al, 2021 ; Graham et al, 2021 ; Kyprianides et al, 2021 ), the impact of COVID-19 on potential trauma exposure has yet to be explored. As such, this paper aims to provide a preliminary exploration into the impact of the pandemic on the type of trauma that officers have been exposed to and, where possible, quantify the scope of these impacts and identify high-risk roles.…”
Section: Introductionmentioning
confidence: 99%